DOSIMETRIC EVALUATION OF POST-MASTECTOMY THREE-DIMENSIONAL CONFORMAL RADIATION THERAPY (3DCRT) BREAST CANCER TREATMENT PLANS - Herwiningsih, Sri; Naba, Agus; Rianto, Sugeng; Hentihu, Fatimah Kunti (Universitas Mataram, 2023)
Breast cancer is the most diagnosed cancer in women globally. External beam radiotherapy is one method to treat breast cancer, which can be given to the patients after mastectomy. The changes in anatomy of breast tissues after mastectomy makes the radiotherapy treatment very challenging to ensure the prescribed dose delivered to the tumour target while the radiation to the surrounding critical organs is kept to be low. This study aims to evaluate the dosimetric parameters of radiotherapy treatment plans for breast cancer patients after mastectomy delivered using 3DCRT technique. The evaluation includes the target coverage to the PTV, defined as the volume of PTV receiving 95% of the prescribed dose and the volume of PTV receiving 107% of the prescribed dose. The min, max and mean dose to the PTV were also recorded. The dosimetric parameters to the OARs were Dmean and V20 to the lung, Dmean and V25 to the heart, Dmean to esophagus and Dmax to the spinal cord. The result shows that target coverage is fulfilled in most of the plans, however the host spot in the PTV also observed in the most of the plans. Dose to heart, left lung, esophagus and spinal cord are relatively low and below the constraint recommended by QUANTEC, however the V20 to the right lung exceeded the constraint in the most of the plans. The combination of photon and electron beam might be useful to reduce the excessive dose to the right lung.